2014
DOI: 10.1007/s11356-014-3597-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of effluent treatment plant during commissioning of activated sludge process unit

Abstract: Industrial effluent treatment plants (ETPs) are very important in protecting the environment and different life forms from harmful industrial waste. Hence, the efficiency of ETPs must be regularly monitored, particularly after major repair or replacement work. Present study evaluated the performance of an ETP over a period of 4 months, during which aeration tank (T1) of the activated sludge unit was replaced with a new one (T2). System had to be maintained operational during this transition, which warranted cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…ETP is very important to protect the environment and different lives from threat of toxic industrial wastewater. So the efficiency of ETPs must be regularly monitored, particularly after major repair or replacement work (Bafana et al 2015). However, the study showed that amongst 9 industries, most of the industries discharged water within DoE prescribed limit and only 3 industries crossed the standards in case of physical parameters.…”
Section: Analysis Of Physical Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…ETP is very important to protect the environment and different lives from threat of toxic industrial wastewater. So the efficiency of ETPs must be regularly monitored, particularly after major repair or replacement work (Bafana et al 2015). However, the study showed that amongst 9 industries, most of the industries discharged water within DoE prescribed limit and only 3 industries crossed the standards in case of physical parameters.…”
Section: Analysis Of Physical Parametersmentioning
confidence: 99%
“…The evaluation of ETP's efficiency is very important to protect environment and public health from dangers of industrial wastewater. Hence, the efficiency of ETPs must be, regularly, monitored (Bafana et al 2015) and present study evaluated the performance of ETPs of different industries at Kalurghat, Chittagong. From (Table 5), it is seen that the study was carried to analyze target heavy metals parameter (e.g., Cr, Pb, Zn, Cu, and Ni) of the outlet of ETPs; there is only Alfa Textile for (Cu, Zn, & Cr), Well Group for Cr and Asian Apparels for Ni that metals content were not within the DoE standards and in the rest industries such parameters were within the DoE prescribed water quality parameters.…”
Section: Analysis Of Chemical Parametersmentioning
confidence: 99%
See 3 more Smart Citations